Evaluation of UMKM Capabilities in Implementing Accounting Applications (Case Study of Inem Catering) - Solar, Fernando Yosua; Khudri, Tubagus Muhamad Yusuf (Dinasti Publisher, 2025)
Inem Katering is a business that is still developing in Minahasa, North Sulawesi, which is engaged in the culinary sector with a focus on catering services for various large events such as weddings, birthdays, funerals, and other thanksgiving events. This business is not yet supported by well-structured financial management. Most of the cash flow is still based on estimates, without clear records. The existence of technology is greatly needed by Inem Katering not only to make it easier to prepare financial reports but also to make this business grow. One of the uses of information technology in helping Inem Katering prepare financial reports can be in the form of the application of accounting software, Accurate. The Technology-Organization-Environment (TOE) framework is used to evaluate the implementation of the accurate accounting application with three contexts, context of technology, organization and environment. This research method uses a quatitative approach obtained from the results of interviews with three sources. The results of the study show that in the context of technology, the relative advantage attribute indicates that the implementation of this accounting application will provide benefits in the form of important information for managers and employees such as balance sheet and profit and loss reports in accordance with SAK EMKM. Meanwhile, for the organizational context at this time, business managers fully support the adoption of this application, but at this time the Katering business has not been able to add special employees to manage the accounting application. Environmental factors are influenced by competition in this business sector, but the implementation of this accounting application can help the Katering business to evaluate their needs for technology.